2023
DOI: 10.1063/5.0124360
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for speckle-scale beam bending in classical ray tracing schemes for propagating realistic pulses in indirect drive ignition conditions

Abstract: We propose a semi-analytical modeling of smoothed laser beam deviation induced by plasma flows. Based on a Gaussian description of speckles, the model includes spatial, temporal, and polarization smoothing techniques, through fits coming from hydrodynamic simulations with a paraxial description of electromagnetic waves. This beam bending model is then incorporated into a ray tracing algorithm and carefully validated. When applied as a post-process to the propagation of the inner cone in a full-scale simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…(11)], indicate an average over a speckle ensemble, ℓ RPP = 45 64 Fλ denotes the speckle correlation length of an RPP beam 13 , and n c the critical density. Similar expressions in the context of beam bending 8,11,20 have been derived, with the dependence on the plasma density n, the average ponderomotive potential ⟨U⟩, and the speckle (or beam) width ∼ Fλ , with F denoting the beam optics Fnumber. Note that the spatially averaged plasma density ⟨n⟩ and the average ponderomotive potential ⟨U⟩/T e normalized to the electron temperature can be assumed to vary slowly on the speckle's width Fλ and response time Fλ /c s .…”
Section: Drag On Plasma Flow Due To Beam Deflectionmentioning
confidence: 71%
See 2 more Smart Citations
“…(11)], indicate an average over a speckle ensemble, ℓ RPP = 45 64 Fλ denotes the speckle correlation length of an RPP beam 13 , and n c the critical density. Similar expressions in the context of beam bending 8,11,20 have been derived, with the dependence on the plasma density n, the average ponderomotive potential ⟨U⟩, and the speckle (or beam) width ∼ Fλ , with F denoting the beam optics Fnumber. Note that the spatially averaged plasma density ⟨n⟩ and the average ponderomotive potential ⟨U⟩/T e normalized to the electron temperature can be assumed to vary slowly on the speckle's width Fλ and response time Fλ /c s .…”
Section: Drag On Plasma Flow Due To Beam Deflectionmentioning
confidence: 71%
“…In absence of flow, a stationary equilibrium can be reached via balance between the local density and the ponderomotive potential, namely ρ 0 = (n e /n 0 ) v ⊥ =0 ≡ exp(−U/T e ). It has, however, been shown that flow can considerably modify the response of the plasma fluid 8,9,[18][19][20] .…”
Section: Transverse Plasma Flow and Beam Deflectionmentioning
confidence: 99%
See 1 more Smart Citation